Can Marijuana Reduce Social Pain?. (March 2014) - Deckman, Timothy; DeWall, C. Nathan; Way, Baldwin; Gilman, Rich; Richman, Stephanie
Social and physical pain share common overlap at linguistic, behavioral, and neural levels. Prior research has shown that acetaminophen—an analgesic medication that acts indirectly through cannabinoid 1 receptors—reduces the social pain associated with exclusion. Yet, no work has examined if other drugs that act on similar receptors, such as marijuana, also reduce social pain. Across four methodologically diverse samples, marijuana use consistently buffered people from the negative consequences associated with loneliness and social exclusion. These effects were replicated using cross-sectional, longitudinal, and experimental designs. These findings offer novel evidence supporting common overlap between social and physical pain processes.